Application of Klampar Batik Branding as A Tactical Image Forming Factor (Case Study of Batik Center, Klampar Village) - A. B. Wibisono; A. T. Artanto; N. Anggriani (Nusantara Science and Technology Proceedings)
Branding in the SMEs (Small and Medium Size Enterprises) centers in the modern era is considered very necessary, so that economic progress and product stability in consumers are maintained dynamically. This research on Klampar Batik is an applied model of the results of previous research in the Batik center. The research with the theme "Applied Branding Model as a Tactical Image Forming Factor (Batik Center Case Study, Klampar Village)" was a continuation of previous research. The problem in this study is, to what extent is the effectiveness of previous research when its application is carried out in the center of Batik. In this study aims to make an analysis of the application and attitudes of society towards Branding that has been made in previous studies, this research is located in Klampar Village, Kecamatan Proppo, Kabupaten Pamekasan. This research is packaged in a community service model that is carried out periodically for two months. The methodology in this study was to conduct Focus Group Discussions (FGD) to village officials and 30 Klampar batik craftsmen. In addition, this research is also supported by journals and literature to provide a concrete picture of the research conclusions.